FIRST STEP TOWARD ESTABLISHING MICROSOFT RESEARCH CENTRE IN INDONESIA - Ma'mun, Nurhayati; Dhewanto, Wawan; Ronaldi, ,; Surendro, Kridanto; Sugiharto, Basuki (SBM ITB, 2007)
This research started when President Yudhoyono visited USA and met with Bill Gates back in 2005. President Yudhoyono later asked Gates to establish Microsoft Research Centre in Indonesia to promote the Indonesian ICT industry. Later that year, the Indonesian Government signed a MOU with the Microsoft Research Centre Asia in Beijing to extend the cooperation between Microsoft and the Indonesian Government. The MOU later took form as Microsoft Innovation Centre in ITB and ITS. The problem arises whether Microsoft will build the Microsoft Research Centre in Indonesia? Will Indonesia be able to become a leading software exporter? How the Microsoft Research centre will someday established in Indonesia. This research later focused on establishing an R&D facility in developing countries. The main concern is Microsoft research center due to its latest agreement with the Indonesian Government. The dilemma facing Microsoft research center establishment in Indonesia is analyzed using Actor-Network Analysis. The software used for this analysis is DANA (Dynamic Actor Network Analysis).The data for input of the software was gained through interviews and secondary data gathering. The issue discussed is whether ITB should involve in establishing Microsoft research center Indonesia or not. The result show that ITB should involve in minimum capacity. The result using simulation and benchmark suggest that Microsoft should begin the establishment of a research centre in Indonesia, not the other way around i.e. academics (ITB) as the primary mover. The Indonesian Government should also induce foreign knowledge-based companies to invest in Indonesia.Â Keywords: Microsoft research centre, feasibility study, technology transfer